Embodied Techniques: The Communal Formation of the Maskil’s Self - Newman, Judith H. (Dead Sea discoveries, 2015)
This article explores the significance of the posture of full prostration by the Maskil that appears uniquely in association with him in the Hodayot. Using theoretical frameworks from ritual studies and embodied cognition, as well as traditional philological work, I argue that the Maskil’s prostration summons the cultural memory of Moses as chief intercessor. This embodied technique serves not only to form the self of the leader in relation to the Yaḥad, but shapes the community that worships with him in the gathered assembly.